Moving to a Circular Economy in China: Transforming Industrial Parks into Eco-industrial Parks. (May 2018) - Mathews, John A.; Tan, Hao; Hu, Mei-Chih
China's moves to introduce a Circular Economy have attracted wide attention as a solution to severe problems of resource inefficiency and lack of resource productivity. This article highlights the distinctive strategy of focusing such efforts on existing industrial parks, turning them into eco-industrial parks. It provides three case studies and highlights the management issues involved as overcoming reverse salients and capturing network advantages. China is an especially instructive case because it starts well behind the Organisation for Economic Co-operation and Development (OECD) countries and thereby has much to gain by adopting comprehensive policies.